2000
DOI: 10.1161/01.str.31.11.2616
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Subtypes of Cerebral Infarction in a General Population

Abstract: Background and Purpose-We estimated the incidence of first-ever cerebral infarction in regard to its subtypes and analyzed their risk factors separately in a community-based prospective cohort study in Japan. Methods-Stroke-free subjects (nϭ1621) aged Ն40 years were followed up for 32 years from 1961. During this period, 298 cerebral infarctions occurred and were divided into 167 lacunar, 62 atherothrombotic, 56 cardioembolic, and 13 undetermined subtypes of infarction on the basis of clinical information incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
246
12
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 328 publications
(286 citation statements)
references
References 44 publications
21
246
12
4
Order By: Relevance
“…Our finding adds to existing evidence that diabetes raises the risk of lacunar infarction in both sexes, since a previous Japanese study showed a significant independent association only among men [4]. It is plausible that glucose abnormality or insulin resistance causes microangiopathy, with arteriosclerosis in small penetrating arterioles of the cerebral basal ganglia, leading to lacunar infarction [16].…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Our finding adds to existing evidence that diabetes raises the risk of lacunar infarction in both sexes, since a previous Japanese study showed a significant independent association only among men [4]. It is plausible that glucose abnormality or insulin resistance causes microangiopathy, with arteriosclerosis in small penetrating arterioles of the cerebral basal ganglia, leading to lacunar infarction [16].…”
Section: Discussionsupporting
confidence: 74%
“…Due to the fact that a previous Japanese study [4] reported that the relationship between diabetes and risk of ischaemic stroke varied according to sex, we conducted sex-specific analyses in addition to sex-adjusted analyses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…21,22 Based on its pathogenesis, stroke is divided into several clinical subtypes, and the effects of BMI on stroke are considered to be different among these subtypes. 8,19 In addition, obesity is an important risk factor for hypertension, diabetes mellitus and dyslipidemia, which are known as major risk factors for stroke, 23,24 and therefore, whether obesity itself independently increases the risk of stroke remains controversial.…”
Section: Introductionmentioning
confidence: 99%